Role of non-lipid risk factors like hs-CRP, uric acid and thyroid stimulating hormone in metabolic syndrome - Babu, V. Srinivasa; Ramaswamy, C.; Chakravarthy, V. Kalyan (International Journal of Research in Medical Sciences, 2018)
Background: Metabolic syndrome is the cluster of diseases which arises due to excess of plasma glucose, cholesterol, fatty acids, blood pressure and obesity. The role of lipids in the development of MetS had been extensively studied. Though some non-lipid factors like hsCRP, uric acid and TSH level also remain elevated in the serum of the MetS patients, the role of these non-lipid risk factors remain incompletely understood. The objective of this study was to investigate which of these factors better predicts Mets, in order to help prevention and early detection of MetS and its associated type 2 diabetes mellitus and cardiovascular diseases. Aim and objectives was to study the significance of serum highly sensitive C-reactive protein (hs-CRP), serum uric acid (SUA) and thyroid stimulating hormone (TSH) levels in metabolic syndrome. Methods: A total of four hundred and fifty subjects (211 men and 239 women) aged ≥35 years attending the hospital were divided into three groups based on the components level of MetS as control (CS), normal (MS) and severe (SMS) MetS groups. Their fasting blood sample were taken and analyzed for the serum hs-CRP, uric acid and TSH levels. The result showed that the mean hs-CRP and uric acid levels were significantly higher in Metabolic Syndrome group (MS) and in Severe Metabolic Syndrome group (SMS) when compared to control group. But the mean TSH levels were more in MS group and in SMS group than the control which was statistically not significant. The analysis of relative significance of these risk factors showed that serum hs-CRP level had a positive linear correlation with the severity of MetS whereas, the TSH level was significantly high only in SMS and the uric acid level was not correlated with the MetS. Results: Our study revealed that type II (absence of sutural bones) was commoner than type I (presence of type I) asterion. The asterion was 4.82±0.58 cm from tip of the mastoid process on the right side and 4.70±0.70 cm on the left. It was greater in males than in females, p value being statistically significant (P = 0.00 and P = 0.02 for right and left sides respectively). The distance of asterion from supramastoid crest was 4.22±0.73 cm on the right and 4.23±0.58 cm on the left. The distance in males was more than in females. The P value 0.00 was statistically significant on the right side. Regarding the position of the asterion in relation to transverse sinus, it was on the transverse sinus in 62% cases, below it in 32% and above in 6%. Conclusions: In the present study, there was higher mean serum hs-CRP level in patients with metabolic syndrome which showed a linear increase with increasing number of components of the metabolic syndrome. Though available literature indicated that hyperuricemia adult subjects tend to develop MetS more frequently our findings showed this increase was not dependent on the severity of MetS. Also, significantly high TSH levels were found only in severe MetS suggest that as per this study the serum hs-CRP values may be consider as the diagnostic criteria for metabolic syndrome and helps to improve future prediction of development of type 2 DM and cardiovascular diseases.